Elaboración de procedimiento operativo estándar para la presentación de expediente técnico básico en un proceso de adquisición de productos farmacéuticos - Guevara Angulo, Gloria Susana (2019)
The objective of this report was to elaborate a Standard Operating Procedure (SOP) with the purpose of standardizing the preparation of technical files for pharmaceutical product acquisition processes, presented by a drugstore, taking into account the current regulations. To this end, the search for the laws and regulations in force was carried out; it was reviewed and analyzed taking into account the most important and necessary for the preparation of the SOP. Finally, the SOP called SOP N ° 001 "Presentation of a technical file in a process of acquisition of pharmaceutical products" was drafted, with a format called FOR-001-01 "Format to formulate Consultations and Observations" and Annexes that will help with a better understanding of the SOP. With the SOP prepared it is expected to minimize or eliminate errors that may occur in the preparation of a technical file for a process of acquisition of pharmaceutical products imported by a drugstore, in the Area of Regulatory Affairs, as well as to facilitate the training of new personnel, and thus ensure that the process is performed correctly based on the current regulations and detailed in the SOP